The teacher commitment and motivation : have they diminished? - Md Nor, Sharifah; Roslan, Samsilah; Mahyuddin, Rahil (Common Ground Publishing, 2009)
This paper discusses findings of a study investigating the changes in psychosocial profiles of secondary school teachers in Selangor. The study involved 304 teachers from 16 secondary schools in Selangor. Data were collected through questionnaires consisting of items measuring changes in teachers’ commitment, motivation and burnout levels. Frequencies, t-test and correlations were the main statistical tools employed. The findings revealed that generally there are significant changes in the current teachers’ commitment and motivation compared to their commitment and motivation in the past. There are negative changes in teachers’ motivation and commitment and an increase in teachers’ burnout levels. Teachers attribute the negative changes mainly to the increase in work load, and the positive changes to their personal development. The findings suggest that there is much to be done to increase teachers’ commitment and motivation and to reduce teachers’ burnout. It is highlighted that teachers’ work load is the main factor that needs improvement.